Profile of central and effector memory T cells in the progression of chronic human chagas disease. - Jacqueline Araújo Fiuza; Ricardo Toshio Fujiwara; Juliana Assis Silva Gomes; Manoel Otávio das Costa Rocha; Ana Thereza Chaves; Fernanda Fortes de Araújo; Rafaelle Christine Gomes Fares; Andrea Teixeira-Carvalho; Olindo de Assis Martins-Filho; Guilherme Grossi Lopes Cançado; Rodrigo Correa-Oliveira (Public Library of Science (PLoS), 2009)
BACKGROUND: Chronic Chagas disease presents several different clinical manifestations ranging from asymptomatic to severe cardiac and/or digestive clinical forms. Several studies have demonstrated that immunoregulatory mechanisms are important processes for the control of the intense immune activity observed in the chronic phase. T cells play a critical role in parasite specific and non-specific immune response elicited by the host against Trypanosoma cruzi. Specifically, memory T cells, which are basically classified as central and effector memory cells, might have a distinct migratory activity, role and function during the human Chagas disease. METHODOLOGY/PRINCIPAL FINDINGS: Based on the hypothesis that the disease severity in humans is correlated to the quality of immune responses against T. cruzi, we evaluated the memory profile of peripheral CD4(+) and CD8(+) T lymphocytes as well as its cytokine secretion before and after in vitro antigenic stimulation. We evaluated cellular response from non-infected individuals (NI), patients with indeterminate (IND) or cardiac (CARD) clinical forms of Chagas disease. The expression of CD45RA, CD45RO and CCR7 surface molecules was determined on CD4(+) and CD8(+) T lymphocytes; the pattern of intracellular cytokines (IFN-gamma, IL-10) synthesized by naive and memory cells was determined by flow cytometry. Our results revealed that IND and CARD patients have relatively lower percentages of naive (CD45RA(high)) CD4(+) and CD8(+) T cells. However, statistical analysis of ex-vivo profiles of CD4(+) T cells showed that IND have lower percentage of CD45RA(high) in relation to non-infected individuals, but not in relation to CARD. Elevated percentages of memory (CD45RO(high)) CD4(+) T cells were also demonstrated in infected individuals, although statistically significant differences were only observed between IND and NI groups. Furthermore, when we analyzed the profile of secreted cytokines, we observed that CARD patients presented a significantly higher percentage of CD8(+)CD45RA(high) IFN-gamma-producing cells in control cultures and after antigen pulsing with soluble epimastigote antigens. CONCLUSIONS: Based on a correlation between the frequency of IFN-gamma producing CD8+ T cells in the T cell memory compartment and the chronic chagasic myocarditis, we propose that memory T cells can be involved in the induction of the development of the severe clinical forms of the Chagas disease by mechanisms modulated by IFN-gamma. Furthermore, we showed that individuals from IND group presented more T(CM) CD4(+) T cells, which may induce a regulatory mechanism to protect the host against the exacerbated inflammatory response elicited by the infection.